Estudio doctrinario y jurídico respecto del derecho a la objeción de conciencia inmiscuido en el ámbito médico: un enfoque desde la eutanasia activa directa garantizando una muerte digna - Ríos Ludeña, Andrés Alonso (2024)
The present research work entitled “Doctrinal and legal study regarding the right to conscientious objection involved in the medical field: an approach from direct active euthanasia guaranteeing a dignified death” has the sole purpose of studying doctrinally and legally conscientious objection. as a fundamental right and its relationship with euthanasia. We will deeply analyze the Ecuadorian regulations in relation to the topic raised, in contrast to other regulations such as Colombian and Spanish regulations, the same ones that have been precursors in the development of euthanasia and dignified death. Our Constitution of the Republic of Ecuador in its article 66, paragraph 12, establishes that the right to conscientious objection may not undermine other rights, nor cause harm to people or nature. Everyone has the right to refuse to use violence and participate in military service. The problem in our country is that there is no regulation that deeply develops, nor relevant jurisprudence that gives us a greater understanding regarding the scope of this right, that is, in our country an in-depth diagnosis has not been demonstrated in the regulations. about the right to conscientious objection, nor does it exist in euthanasia, which is the topic we are going to raise, in the same way there is no greater jurisprudence to determine to what extent the person, and in this case the doctor, goes in the objection of conscience, therefore, one may have some ethical and moral problems when making a decision. On the other hand, conscientious objection does not have a legal guideline in the judgment, which, within the Ecuadorian Constitution, is directly applied when applying the norm, because there is a conflict of rights. For this reason, I have proposed raising awareness among the respective bodies in order for them to arbitrate the pertinent measures, as well as proposing that regulations be created to regulate this right due to the limited development that conscientious objection has had over time, in a special way relating to the medical field and the figure of euthanasia. For the corresponding development of this work, some investigative variables such as doctrinal and legal variables have been established. The exploration we carried out is doctrinal and legal, in addition the methods and instruments were key to proposing the solution to the existing problem. Regarding the instruments, surveys, interviews and case studies were applied, focusing on some legal criteria of legal professionals, which allowed us to obtain conceptual clarity in fundamental rights and medical practice.